PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR IPA SISWA MENGGUNAKAN MODEL KOOPERATIF TIPE PICTURE AND PICTURE DI SD 009 KUALA TERUSAN PANGKALAN KERINCI - Sefriyatni Sefriyatni (STKIP Pesisir Selatan, 2020)
The learning implementation problems found in elementary school 009 Kuala Terusan are the low activity and learning outcomes of students who reach standards in science learning in grade IV. For this reason, the picture and picture type cooperative model is applied. The objectives of this study were 1) to determine the effectiveness of the picture and picture cooperative model in increasing students' learning activeness in Science and 2) to determine the effectiveness of the picture and picture cooperative model in improving the learning outcomes of fourth grade students of elementary school 009 Kuala Terusan. This type of research is classroom action research. The duration of this research was from October to November 2019. The subjects of this study were fourth grade students of the 2019/2020 school year 009 Kuala Terusan public elementary school. The instrument used was the observation sheet and student learning outcomes. The data analysis technique used is descriptive analysis technique. The results of this study are 1) The picture and picture type of cooperative learning model is effectively applied in science learning materials for processing waste and used goods and the properties of light in the 009 Kuala Terusan elementary school to increase the active involvement of students in learning .; and 2) The picture and picture type of cooperative learning model is effectively applied in science learning at 009 Kuala Terusan elementary school to improve student learning outcomes from the original number of students with completeness levels up to 90.3%.